Hue-based quantification of mechanochromism towards a cost-effective detection of mechanical strain in polymer systems. Issue 1 (8th December 2016) - Battisti, A.; Minei, P.; Pucci, A.; Bizzarri, R.
Abstract : Hue evaluation from HSV colour space provides a fast and cost-effective tool for the detection of deformation in polymers loaded with the mechanosensitive fluorescent dye BBS. Abstract : HSV is a digital colour space easily accessible by the transformation of RGB images. In this work, the hue parameter H was used to assess mechanically induced colour changes of the aggregation-sensitive fluorescent dye 4, 4′-bis-(2-benzoxazolyl)stilbene (BBS), thus implementing a cheap and reliable method for the detection of mechanical deformation in a polymer matrix.